Pathogenicity of Beauveria bassiana isolates toward Leptinotarsa decemlineata [Coleoptera : Chrysomelidae], Myzus persicae [Homoptera : Aphididae] and their predator Coleomegilla maculata lengi [Coleoptera : Coccinellidae] - Todorova, S.I.; Coderre, D.; Côté, J.-C. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 2000)
Ten isolates of Beauveria bassiana from different sources and geographical sites were evaluated under laboratory conditions at a concentration of 107 conidia ml-1 for their pathogenicity against two insect pests, the Colorado potato beetle (Leptinotarsa decemlineata) and the green peach aphid (Myzus persicae), and their predator, the spotted ladybird beetle (Coleomegilla maculata lengi). Six isolates were highly virulent to all three insect species. Four others showed different degrees of specificity. The isolates 49, 233 and 210087 were the most interesting for their potential development as biological control agents because they were highly virulent for the two insect pests and caused low mortality in the coccinellid.